Ethics of Using Social Media with Principle Islamic Communication - Rubino; Putri Rahmadani Zein (Sean Institute, 2022)
In an Islamic perspective, communication is an inseparable part of human life because all of our steps are always accompanied by communication. The communication in question is Islamic communication, namely ethical communication. Communication sourced from the Koran and hadith. The message of the Prophet Muhammad SAW has a broad meaning that in communicating should be in accordance with the facts that we see, hear, and experience. These ethical principles can actually be used as a basis for every Muslim when carrying out the communication process, both in daily interactions, preaching, and other activities. This journal explains the ethics of communication contained in Islamic teachings, so that in terms of communicating Islam it regulates people with the aim of harmonious communication and good social relations, so that every individual feels safe and comfortable when collaborating to fulfill their life needs. Social media is a new media where everyone can become a journalist to make information and spread it, so that self-awareness and ethics are needed in using social media.